1997
DOI: 10.1097/00004872-199715120-00074
|View full text |Cite
|
Sign up to set email alerts
|

Plasma atrial natriuretic peptide and natriuretic peptide receptor gene expression in adipose tissue of normotensive and hypertensive obese patients

Abstract: Our data suggest that in obese hypertensives compared to obese normotensives, the lower NPr-A: NPr-C ratio might determine decreased biological activity and/or an increased clearance of natriuretic peptide in adipose tissue, suggesting that the natriuretic peptide and its receptor system may be important in obesity-related hypertension where ANP levels are lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
2
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(161 citation statements)
references
References 24 publications
7
149
2
3
Order By: Relevance
“…Patients with T2DM tend to be obese (the median body mass index in LANCET was 35 kg/m 2 ), and obese patients have NT‐proBNP concentrations that are 10% to 30% lower than the nonobese, perhaps because of the hyperinsulinemia and insulin resistance commonly observed in obese patients 26, 27. Some have postulated that this natriuretic “handicap” might partially explain the susceptibility of obese and overweight individuals to salt retention, hypertension, and heart failure 27, 28. We and others have published evidence that elevations in NPs are associated with decreased incidence of diabetes mellitus,15, 29 and Mendelian randomization studies have suggested that these associations may be causal in nature 16.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T2DM tend to be obese (the median body mass index in LANCET was 35 kg/m 2 ), and obese patients have NT‐proBNP concentrations that are 10% to 30% lower than the nonobese, perhaps because of the hyperinsulinemia and insulin resistance commonly observed in obese patients 26, 27. Some have postulated that this natriuretic “handicap” might partially explain the susceptibility of obese and overweight individuals to salt retention, hypertension, and heart failure 27, 28. We and others have published evidence that elevations in NPs are associated with decreased incidence of diabetes mellitus,15, 29 and Mendelian randomization studies have suggested that these associations may be causal in nature 16.…”
Section: Discussionmentioning
confidence: 99%
“…Increased LV mass/BSA but normal RWT identified eccentric LV hypertrophy, whereas increases in both variables identified concentric LV hypertrophy. 2,27,28 LV internal dimension and wall thickness were measured at end-diastole and end-systole following ASE recommendations 13 on Ն3 cardiac cycles. When optimal orientation of the M-mode cursor could not be obtained, correctly oriented linear dimension measurements were made using 2Dimensional imaging by the leading-edge ASE convention.…”
Section: Echocardiographymentioning
confidence: 99%
“…This is also supported by previous observations that hyperinsulinemic 22 or obese 23 subjects are more sensitive to sodium load because of reduced effect of atrial natriuretic peptide, 24 -26 partly attributable to an increased clearance in adipose tissue. 27,28 This may also relate to Nt-proBNP, but the importance of the natriuretic clearance receptor C for clearance of Nt-proBNP is unknown. 29 Alternatively, BNP or Nt-proBNP may, through lipolytic and lipomobilizing effects, change the metabolic state as demonstrated for atrial natriuretic peptide 30 and reduce the incidence of overweight and obesity.…”
Section: Olsen Et Al Natriuretic Peptides and The Metabolic Syndromementioning
confidence: 99%
“…[1][2][3] In several studies, plasma ANP and BNP concentrations have been found to be decreased in obese subjects. [4][5][6][7] Additionally, an increase in natriuretic peptides (NPs) has been reported to parallel an increase in blood pressure. 8 Either by boosting the sympathetic activity, increasing sodium and water reabsorption or upregulating the angiotensinogen type 1 receptors, insulin resistance can lead to the inextricable component of obesity and hypertension.…”
Section: Introductionmentioning
confidence: 99%